The Role of Guidance and Counseling Teachers in the Independent Learning Curriculum for the Formation of Student Character - Tiara Afrillia; Yenti Arsini (Edumaspul: Jurnal Pendidikan, 2024)
The Independent Learning Curriculum aims to improve the quality of education and produce graduates who are qualified, innovative, and able to compete globally. Guidance and counseling services can be used as a means to achieve the educational goals of the Independent Learning Curriculum. The role of guidance and counseling teachers in developing good character dimensions in the concept of the independent curriculum is something new. This research aims to examine the role of guidance and counseling teachers in shaping student character through the Independent Learning Curriculum at SMA N 2 Tebing Tinggi. The research method used is descriptive qualitative with data collection techniques through interviews and observations. The results of the study show that Guidance and Counseling (BK) Teachers at SMA Negeri 2 Tebing Tinggi play a crucial role in shaping student character in accordance with the principles of the Independent Learning Curriculum. This role includes the preparation of programs that not only focus on academic achievement, but also on developing student character such as responsibility, honesty, and independence. The guidance and counseling teacher at SMA Negeri 2 Tebing Tinggi applies various innovative and adaptive strategies in forming student character in accordance with the principles of the Independent Learning Curriculum.